TGF-β1 role in uterine leiomyoma and endometrial polyp: an insight to drug-based treatment instead of surgical techniques - Azam Faraji; Rezvan Shamsadinimoghadam; Mojgan Akbarzadeh Jahromi; Niloofar Namazi (Korean Society of Obstetrics and Gynecology, 2021)
Objective Considering the high prevalence of leiomyoma and endometrial polyps, investigating the contributing factors and determining the pathophysiology of these lesions are essential. Target therapy is now an acceptable method for the treatment of some diseases. We aimed to determine the expression of transforming growth factor (TGF)-β1 in endometrial polyps and leiomyomas to discover a drug-based method to overcome surgical treatments. Methods In this cross-sectional study, 55 patients with leiomyoma and 55 patients with polyps were included. Prepared slides from leiomyoma and adjacent myometrium or polyp lesions and adjacent endometrium were obtained and investigated for TGF-β1. Then, data were collected and analyzed using SPSS version 22. Results The mean age of participants was 40.6±5.8 years. Based on their reports, 88.2% (n=97) of patients in the study population had abnormal uterine bleeding with similar distributions among both groups. In contrast, 63.5% of the leiomyoma group did not express TGF-β1. However, in normal myometrium, 23.6% had the highest degree of TGF-β1 expression. Polyp tissue did not show staining for TGF-β1 in any patients. Additionally, 89.1% of non-polypoid endometrium did not express TGF-β1. Normal tissue had a significantly greater amount of TGF-β1 compared to leiomyoma and endometrial polyps. Conclusion TGF-β1 is expressed more prominently in normal myometrium with mostly high-intensity features compared to leiomyoma. Additionally, polyps showed no staining for TGF-β1, while normal endometrium showed a low-density staining pattern.